Digital X-Ray Apparatus Based on the Scanning R-Ray Gas-Discharge Detector for Studying of Interior Structure of Biological Objects; Advanced Materials Research : Advanced materials, synthesis, development and application; Vol. 880 : Prospects of Fundamental Sciences Development (PFSD-2013) - Stuchebrov S. G. Sergey Gennadevich; Verigin D. A. Dan Aleksandrovich; Lukyanenko Y. Yelena; Siniagina M. Maria; Wagner A. R. Aleksandr Rudolfovich (2014, 2014)
Title screen